1035325 Suplementasi Vitamin B1 dan B6 Sebagai Tatalaksanan Hiperemesis Gravidarum - Annisa (STIKes Budi Mulia Sriwijaya, 2019)
ABSTRACT Hiperemesis gravidarum is a severe disease of nausea and vomitting accompanied by anorexia and associated with early pragnancy. Hiperemesis gravidarum often lead to dehidration and weigth loss. Thin situation occurs in 0,3-2% of pregnancies. Pragnancy with hiperemesis gravidarum has potential effect to cause fetal disorder such as preterm birth, low birth weight. Management of hyperemesis gravidarum is supportive. Vitamin B1 (thiamin) and B6 (pyridoxine) are water-soluble vitamins. During parenteral glucose management in inadequate hyperemesis gravidarum with oral intake, requires vitamin B1 supplementation to avoid acute neurological symptoms such as wernicke’s encephalopathy. Vitamin B6 supplementation usually combined with doxylamine can reduce symptoms of nausea and vomiting in hyperemesis gravidarum and have lower side effects. Keywords: Hiperemsis gravidarum, vitamin B1, vitamin B6